(untitled) (Tempo e Argumento, 2016)
Humor is defined as a way of presenting, judging, or commenting on reality, emphasizing the comical or ridiculous side of things in different situations and having different purposes. For the Polish people, humor has always served as another tool to face reality at difficult moments of its history. In this study, we take the assumption that at the time of the so-called real socialism in Poland the Polish people used humor as one of the most important ways of resisting the system, as well as maintaining self-esteem and common sense before some truly absurd times. Taking into account that socialism is an ideology that advocates for equal rights, opportunities, and happiness and that real socialism, on its turn, completely denies them to citizens, we organize this study by using Maslow’s Pyramid of Needs. Keywords: Humor; Dictatorship; Real Socialism; Pyramid of Needs; Poland.